Oscillation of Second Order Nonlinear Differential Equations - S.M. Nababan (Journal of Mathematical and Fundamental Sciences, 1996)
In this paper we consider the following second order nonlinear differential equations:u" + f(t,u) = 0, tâ‰¥0Oscillation criteria for the above equation will be established by modification of the method that has been used previously. The results obtained will contain and improve the previous results. Some conditions imposed in the theorem will be less weaker than used before. Tulisan ini membahas persamaan diferensial nonlinear orde dua yang berbentuk:u " + f ( t , u ) = 0 , t>0Kriteria oskilasi untuk persamaan di atas dikaji dengan memodifikasi metode yang pernah dilakukan untuk menentukan kriteria oskilasi untuk persamaan diferensial di atas. Hasil yang diperoleh memuat dan mengembangkan kriteria oskilasi sebelumnya. Beberapa asumsi dalam teorema lebih lemah dibandingkan dengan yang digunakan sebelumnya.